A Study on the Membership Pattern vis-à-vis Lending by Urban Cooperative Banks in Gulbarga District, Karnataka - Rao K, Prashanth; PR Ramakrishnan, Dr. (International Journal of Engineering and Technology, 2018)
The member-driven cooperative banks have rendered yeoman service to the society.  Promoters of these institutions, in line with the guidelines issued by the Reserve Bank of India, have offered membership for prospective borrowers and thus, earned its own place in the Indian financial system.Gulbarga is an important city in northeast Karnataka.  It is located on the Chennai-Mumbai rail route.  It is surrounded by many important places of interest.  Therefore, its location holds significance.Cooperative banks have not been active in this district.  The total credit disbursed reduced from around Rs. 130 crores in 2014-15 to about Rs. 125 crores in 2016-17.  The profit earned by all the banks put together has been around Rs. 3 crores.This study has been undertaken to assess the nature of increase in membership and its relationship with credit disbursed by the Urban Cooperative Banks in Gulbarga district, Karnataka.